1999
DOI: 10.1557/s1092578300002611
|View full text |Cite
|
Sign up to set email alerts
|

Disordering of InGaN/GaN Superlattices after High-Pressure Annealing

Abstract: Interdiffusion of In and Ga is observed in InGaN multiple-quantum-well superlattices for annealing temperatures of 1250 to 1400°C. Hydrostatic pressures of up to 15 kbar were applied during the annealing treatments to prevent decomposition of the InGaN and GaN. In as-grown material, x-ray diffraction spectra show InGaN superlattice peaks up to the fourth order. After annealing at 1400°C for 15 min, only the zero-order InGaN peak is observed, a result of compositional disordering of the superlattice. Compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…However, it should be noted that similar annealing conditions as those used in this study were used for InGaN QW based LED structures and evidenced the loss of QW emission already at 1100 ºC 20 suggesting that sample structure and native defects play an important role in the sample's response to thermal treatment. For example the enhancement of In-Ga interdiffusion in the presence of Mg was suggested by McCluskey et al who observed similar effects of HTHP annealing as presented here but starting at slightly lower temperatures 14 . Such discrepancies between the responses of different InGaN/GaN QWs to annealing are complicating the optimization of annealing parameters for QWI.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, it should be noted that similar annealing conditions as those used in this study were used for InGaN QW based LED structures and evidenced the loss of QW emission already at 1100 ºC 20 suggesting that sample structure and native defects play an important role in the sample's response to thermal treatment. For example the enhancement of In-Ga interdiffusion in the presence of Mg was suggested by McCluskey et al who observed similar effects of HTHP annealing as presented here but starting at slightly lower temperatures 14 . Such discrepancies between the responses of different InGaN/GaN QWs to annealing are complicating the optimization of annealing parameters for QWI.…”
Section: Discussionsupporting
confidence: 87%
“…These authors showed that implantation can significantly enhance the intermixing process. In nitrides this subject has not been studied in detail yet although tunable emission upon intermixing of InGaN/GaN QWs was predicted early by theory and also evidenced experimentally 13,14 . The effectiveness of band profile engineering has recently been shown for staggered InGaN/GaN QW where compositional gradients of QWs have been achieved during the growth 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Our results are consistent with previous studies where a thermal anneal temperature of 900°C was not sufficient to cause any structural changes within the active region. Chuo et al 18 reported that thermal annealing at 900°C produces photolumi-nescence ͑PL͒ similar to as-grown samples and that when higher thermal anneal temperatures are used a blueshift of the PL is detected as a result of intermixing, while the work of McCluskey et al 21 shows that it is not until a thermal anneal temperature above 1200°C is used that a blueshift is detected in the spontaneous emission. The electroluminescent emission spectra of the LEDs annealed at different temperatures are shown in Fig.…”
Section: Havementioning
confidence: 99%
“…Previous studies have shown that intermixing of the InGaN QWs and GaN barriers can occur during thermal annealing. [17][18][19][20][21] Our absorption results imply that any intermixing of the InGaN QW and GaN barriers within these structures has not occurred over the range of anneal temperatures ͑700-900°C͒ used in this study. Our results are consistent with previous studies where a thermal anneal temperature of 900°C was not sufficient to cause any structural changes within the active region.…”
Section: Havementioning
confidence: 99%
“…Layer intermixing in GaN/AlGaN heterostructures with no impurities is observed at temperatures of ϳ1500°C. 6 Other reports of layer disordering of III-nitrides claim only localized intermixing in AlGaN/GaN observed at line defects, 7 or with InGaN/GaN heterostructures at temperatures much higher than the InGaN growth temperature 8,9 making it unclear if an IILD process is occurring.…”
mentioning
confidence: 99%